Agalmatofilia, El Trastorno del Siglo XXI - Quizhpe Calva, Vanesa Jasmin (2025)
In understanding human behavior, psychological science has provided significant advancements and contributions. However, there are still dimensions that have not been fully explained or understood, one of which is human sexuality. This area includes a broad spectrum of atypical behaviors, such as Agalmatophilia, defined as a sexual attraction to inanimate objects like mannequins and inflatable dolls. The objective of the research was to establish the etiology, comorbidity, and symptomatology of Agalmatophilia and to design an informational guide to address the issue. In this study, the method of bibliographic synthesis was used in a qualitative, nonexperimental, cross-sectional design, with exploratory, descriptive, and explanatory scopes. The sample consisted of 10 bibliographic sources and 4 documented cases. The analyzed information revealed that there is insufficient scientific evidence on Agalmatophilia. Nevertheless, it was determined that its causes are related to psychological factors, a history of mental disorders, and neurological factors. A number of additional factors are involved, such as sexual elements associated with objectivity and control, fantasies, pansexuality, abstinence, as well as social factors associated with romantic experiences and traumatic breakups. It was also found that comorbid disorders associated with Agalmatophilia include addiction, PTSD, social anxiety disorder, anxiety-related disorders, delusional disorder, schizophrenia, schizoid personality disorder, OCD, and impulse control disorders. It is important to note that these disorders can be both causes and effects of Agalmatophilia. Additionally, symptoms related to the sexual response cycle and to the psychosocial domain were identified as part of its symptomatology. The findings highlighted the importance of creating an informational guide to educate about sexual disorders. In order to foster understanding and acceptance of diverse forms of sexual expression, these issues must be addressed from an inclusive and stigma-free perspective